Autophagy and the Cell Cycle: A Complex Landscape - Mathiassen, Søs Grønbæk; De Zio, Daniela; Cecconi, Francesco (Frontiers in Oncology, 2017)
Autophagy is a self-degradation pathway, in which cytoplasmic material is sequestered in double-membrane vesicles and delivered to the lysosome for degradation. Under basal conditions, autophagy plays a homeostatic function. However, in response to various stresses, the pathway can be further induced to mediate cytoprotection. Defective autophagy has been linked to a number of human pathologies, including neoplastic transformation, even though autophagy can also sustain the growth of tumor cells in certain contexts. In recent years a considerable correlation has emerged between autophagy induction and stress-related cell cycle responses, as well as unexpected roles for autophagy factors and selective autophagic degradation in the process of cell division. These advances have obvious implications for our understanding of the intricate relationship between autophagy and cancer. In this review, we will discuss our current knowledge of the reciprocal regulation connecting the autophagy pathway and cell cycle progression. Furthermore, key findings involving non-autophagic functions for autophagy-related factors in cell cycle regulation will be addressed.